ANALISIS KESALAHAN PENGGUNAAN PRONOUNS OLEH SISWA KELAS XII BAHASA SMA N 1 TOMBARIRI - TURERE, REGINA LUCIANA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This research entitled â€œAnalisis Kesalahan Pronouns oleh Siswa Kelas XII Bahasa SMA N 1 Tombaririâ€ is an attempt to identify, classify and analyze errors in the use of pronouns made by students of SMA N 1 Tombariri. The method used in this research is descriptive. Aarts and Aartsâ€™ (1982) theory is used to identify and classify the types of pronouns and Ellis (1998) theory is used to analyze the types of pronouns errors made by students of SMA N 1 Tombariri. The data of this research were taken from the studentsâ€™ assignment. The result of this research shows that there are three kinds of errors made by the students. First, omission is to omit a pronoun that is required for an utterance to be considered grammatical. Second, misinformation is the use one pronoun unproperly. Third, misordering is putting the pronouns in an utterance in the wrong order. Â  Keywords : Error analysis, pronouns, omission, misinformation, misordering